METRUM W "POETYCE" MARKA HIERONIMA VIDY - Lew, Agnieszka Paulina (Collectanea Philologica, 2013)
In his Poetics, Vida extols the hexameter, versus heroicus, as the noblest metre. Although herecommends Virgil as the most perfect model for imitation, he himself uses the much freerhexameter of Horace, who not always takes care to make the ictus agree with the word accent inthe last two feet, and sometimes breaks the Laws of Lachmann-Norden, Haupt and Marx. Thanksto the critical edition of Vida’s didactic poem, it is possible to observe the author’s work on themetre – he eliminates some clumsy lines that occur mainly in the Poetics preserved in the VenturiCodex (V).